Telemedicine in palliative care during the COVID-19 era: A review of the literature - Noer Diana Holida; Setiyo Adi Nugroho (Universitas Muhammadiyah Magelang, 2022)
Telemedicine has become an effective approach for managing COVID-19 and preventing the risk of cross-contamination. The health application is growing rapidly, where medical information is transferred via telephone, Internet and other networks for consultation, control medical procedures or examinations. The application is very important to use in the pandemic era in reducing the COVID-19 infection, especially in palliative care. The study aimed to determine Telemedicine's effectiveness on palliative care during the COVID-19 pandemic. The study used a literature review method. Search databases, including Google Scholar, Science Direct, and ProQuest, with the keyword telemedicine for palliative care during the COVID-19 pandemic. The review explained that Telemedicine can establish effective nurse-patient communication, increase safety, improve palliative care and patient support services, reduce APD consumption, and simplify clinical workflows. It also improves patient comfort, reduces the psychological burden of isolation, and reduces nurses' workload. Keywords: COVID-19; telemedicine; healthcare services; technology in health; role of nurses